Pathogenicity And Immunogenicity Of Egg-Adapted Very Virulent Infectious Bursal Disease Virus Isolated In Malaysia - Hashim, Thuzar Than @ Hafiza (2004)
The emergence of very virulent infectious bursal disease virus (vvIBDV) strains caused a devastating economic loss to the chicken industry in Malaysia in 1990. The recurrence of infectious bursal disease (IBD) outbreaks and vaccine failure occurred recently. It is very important to study the pathogenicity, immunogenicity and molecular characteristics of these vvIBDV isolates which are prerequisite before developing the IBD vaccine and testing it in the farms. In this study, UPM 93273 (passage 1 to 48 in chorio-allantoic membrane) was characterized by focusing on the hypervariable region of the VP2 protein. The UPM 93273 isolate was selected among seven other isolates obtained from field outbreaks in layer, broiler and indigenous (village) chickens in various areas in West Malaysia during 1993 to 1994. The sequence of the hv region was obtained following total RNA extraction from the wild type UPM 93273 and its different derivative passages. The hv region was amplified by RT-PCR assay and cloned into pCR-TOPO cloning vector. The right clone harboring the hv fragment was selected by EcoRI restriction enzyme digestion. Finally the cloned fragment was sequenced. The nucleotide and the deduced amino acid sequence alignment and analysis was carried out by using the Bio-Edit software. As a result, markers for very virulent IBDV strain were found in UPM 93273 isolate (wild type to passage 48). The UPM 93273 was found to be very immunogenic but also highly pathogenic. The pathogenicity is reduced during the serial passages in embryonated SPF chickens at passage 31. The passage 31 (P31) of UPM 93273 isolate provided protection against the challenge virus with some degree of bursal atrophy. An effective vaccine depends not only on the full attenuation and genetic stability of the virus strain but also on the route of vaccination. This latter was investigated to determine the immune response of the lymphoid organs against IBDV UPM 94283 strain. Ultrastructural, histopathological and immunohistochemistry studies showed that immunocompetent cells were present in the Harderian gland and were involved in the early and strong immune response against IBDV UPM strain administered via ocular route. Thus, this route can stimulate the lymphoid cells in the Harderian gland, and support the proliferation of lymphoid cells in the bursa before the virus reaches the primary target organs. In addition to this rapid immunogenic reaction, some viruses may drain into the oral cavity when administered via ocular route. As a result, these viruses can stimulate the intestinal lymphoid aggregates along the intestinal tract. As a conclusion, all of the serially passaged UPM 93273 isolate up to passage 48 was found to be still unstable and not sufficiently attenuated indicated by virulence markers which are still conserved. The decrease in the virulence and the pathogenicity seen in the serially passaged strain might be due to other unknown factors. Consequently the risk of reversion to the very virulent state is very high. The current numbers of passages are not sufficient and further passages are necessary in order for the virus to reach a fully attenuated and genetically stable state.